Dynamical evolution of rotating globular clusters with embedded black holes - Fiestas, José (2006)
In this dissertation evolution of self-gravitating dense stellar systems (e.g. globular clusters, galactic nuclei) with embedded black holes is investigated, motivated by observational evidences of the existence of central dark objects in these systems. The interaction between the stellar and black hole component is followed in a way, different from most other investigations in this field, as flattening of the system due to differential rotation is allowed. The axisymmetric system is modelled using 2-dimensional, in energy and z-component of angular momentum, Fokker Planck numerical methods. The interplay between velocity diffusion due to relaxation and black hole star accretion is followed together with cluster rotation. The results show how angular momentum transport andstar accretion support the development of central rotation in relaxation time scales. Gravogyro and gravothermal instabilities conduce the system to a faster evolution leading to shorter collapsetimes with respect to models without black hole, and a faster cluster dissolution in the galactic tidal field of a parent galaxy. As a further application, two-dimensional distribution (in the meridional plane) of kinematical and structural parameters (density, dispersions, rotation) are reproduced, covering a wide range of ages, rotation, concentrations and ellipticities, with the aim toenable the use of set of models for comparison with observational data.